Clinical predictors of proteinuric remission following an LN flare - evidence from the UK JSLE cohort study - Eve M. D. Smith; Peng Yin; Andrea L. Jorgensen; Michael W. Beresford; on behalf of the UK JSLE Study Group (BMC, 2018)
Abstract Background Proteinuria is a well-known risk factor for progression of renal dysfunction in a variety of chronic kidney diseases. In adult-onset Systemic Lupus Erytematosus (SLE) patients with lupus nephritis (LN), proteinuria takes a significant period of time to normalise, with proteinuric remission being associated with improved renal survival and reductions in mortality. The length of time required to attain proteinuric remission has not previously been investigated in Juvenile-onset SLE (JSLE). The aim of this study was to elucidate when proteinuric remission occurs, and whether clinical/demographic factors at LN onset bear influence on the time to proteinuric remission. Methods Participants of the UK JSLE Cohort Study and Repository were included if they had active LN (renal biopsy and/or renal British Isles Lupus Assessment Grade (BILAG) score defined active LN) and proteinuria. Univariate Cox proportional hazard regression modelling was used to explore factors associated with time to proteinuric recovery. Covariates with p-value < 0.2 were included in a multivariable Cox regression model, and backward stepwise variable selection applied. Result 64/350 (18%) of UK JSLE Cohort Study patients fulfilled the study inclusion criteria. 25 (39%) achieved proteinuric remission within a median of 17 months (min 2.4, max 78). Within a multivariate Cox proportional hazard regression model, age at time of LN flare (p = 0.007, HR 1.384, CI 1.095-1.750), eGFR (p = 0.035, HR 1.016, CI 1.001-1.030) and haematological involvement (p = 0.016, HR 0.324, CI 0.129-0.812) at the time of LN onset were found to be significantly associated with time to proteinuric recovery. Conclusions A significant proportion of children with LN have on-going proteinuria approximately two years after their initial flare. Poor prognostic factors all at time of LN onset include younger age, low eGFR, and concomitant haematological involvement.